The cinema of Robert Rodriguez - Aldama, Frederick Luis, 1969- (University of Texas Press, 2014)
Robert Rodriguez stands alone as the most successful U.S. Latino filmmaker today, whose work has single-handedly brought U.S. Latino filmmaking into the mainstream of twenty-first-century global cinema. Rodriguez is a prolific (eighteen films in twenty-one years) and all-encompassing filmmaker who has scripted, directed, shot, edited, and scored nearly all his films since his first breakout success, El Mariachi, in 1992. With new films constantly coming out and the launch of his El Rey Network television channel, he receives unceasing coverage in the entertainment media, but systematic scholarly study of Rodriguez?s films is only just beginning. The Cinema of Robert Rodriguez offers the first extended investigation of this important filmmaker?s art. Accessibly written for fans as well as scholars, it addresses all of Rodriguez?s feature films through Spy Kids 4 and Machete Kills, and his filmmaking process from initial inspiration, to script, to film (with its myriad visual and auditory elements and choices), to final product, to (usually) critical and commercial success. In addition to his close analysis of Rodriguez?s work, Frederick Luis Aldama presents an original interview with the filmmaker, in which they discuss his career and his relationship to the film industry. This entertaining and much-needed scholarly overview of Rodriguez?s work shines new light on several key topics, including the filmmaker?s creative, low-cost, efficient approach to filmmaking; the acceptance of Latino films and filmmakers in mainstream cinema; and the consumption and reception of film in the twenty-first century.